Recovery, Extension and Installation of the City Museum in the Convent of Jesus, Setúbal. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
A defence system was then installed which allowed the original level of the floor inside the building to be restored, re-establishing the original proportion of the spaces on the ground floor – replacing the scale of the monument and bringing it closer to what would have been its initial configuration. And unlike the intervention carried out at the Monastery of Flor da Rosa – where financial restrictions, added to the inexistence of problems of constructive inoperability, would have led to essentially accepting the pre-existing building as it was – in this case – where the fragile limestone masonry walls were practically on the verge of collapse – it became necessary to demolish the concrete elements introduced during the 20th century, taking the weight off the walls. They were replaced by timber construction systems which, although contemporary in design, are very close to the construction logic of the original building.